Repeating a familiar pattern in a new way: The effect of exploitation and exploration on knowledge leverage behaviors in technology acquisitions - Choi, Seungho; McNamara, Gerry (Strategic Management Journal, 2018)
[Research summary: We identify two types of knowledge leverage behaviors undertaken by acquiring firms: integrated and independent knowledge leverage. We address how the prior exploitation or exploration orientation of acquirers influence these two modes of knowledge leverage behaviors. The degree of exploitation of acquirers promotes integrating their existing knowledge with acquired knowledge in innovative actions. In contrast, the degree of exploration of acquirers increases the likelihood that new innovations will use acquired knowledge without integrating it with their prior knowledge. In addition, the firm's prior acquisition rate moderates the relationship between the acquiring firms' previous exploitation or exploration orientation and their knowledge leverage mode. The findings of this article suggest that preacquisition innovation capabilities are distinct from but influence the post-acquisition innovation actions. Managerial summary: Firms often undertake acquisitions to gain access to new knowledge, but they can differ dramatically in how they leverage acquired knowledge. We show that the firm's prior innovation patterns drive this choice. Firms that have previously focused on incremental innovations in their internal innovation efforts tend to integrate acquired knowledge with their own prior knowledge. In contrast, firms that have previously pursued bold innovations tend to leverage acquired knowledge alone in new innovations. Thus, we show that firms use acquisitions as a means to extend their internal innovation patterns—firms that have focused on incremental innovations extend that with acquisitions by linking new innovations to their prior knowledge while firms that have pursued bold initiatives use acquired knowledge to move in new technology directions.]